2004
DOI: 10.1002/aoc.668
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and antimicrobial studies on new gold(I) complexes of imidazolidin‐2‐ylidenes

Abstract: Six new 1,3-diorganylimidazolidin-2-ylidene (NHC) gold(I) complexes of the type [Au(NHC) 2 ] + (1-6), were synthesized by reacting [AuCl(PPh) 3 ] with 1,3-dimesitylimidazolidin-2-ylidene or bis(1,3-dialkylimidazolidin-2-ylidene). The complexes 1-6 were fully characterized by elemental analyses and spectroscopic data. The placement of mesityl or para-substituted benzyl groups on the nitrogen atoms of the ring of the complexes leads to the particularly active antibacterial agents evaluated in this work. It is wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…However, reaction of the cyanoethyl substituted imidazolium salt 1b under similar reaction conditions gave the monocarbene complex [PdBr 2 ( etCN NHC)(imd)] (5) with a N-coordinated mesitylimidazole ligand (imd), which presumably resulted from N-C cleavage of the ß-cyanoethyl group under the basic and relatively harsh reaction condition [6]. Similar cleavage was observed in the analogous reaction of the esterethyl substituted imidazolium salt 2b resulting in complex [PdBr 2 ( etCO2Me NHC)(imd)] (6) (Scheme 3b).…”
Section: Synthesis Of Pd-nhc Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reaction of the cyanoethyl substituted imidazolium salt 1b under similar reaction conditions gave the monocarbene complex [PdBr 2 ( etCN NHC)(imd)] (5) with a N-coordinated mesitylimidazole ligand (imd), which presumably resulted from N-C cleavage of the ß-cyanoethyl group under the basic and relatively harsh reaction condition [6]. Similar cleavage was observed in the analogous reaction of the esterethyl substituted imidazolium salt 2b resulting in complex [PdBr 2 ( etCO2Me NHC)(imd)] (6) (Scheme 3b).…”
Section: Synthesis Of Pd-nhc Complexesmentioning
confidence: 99%
“…All Pd-NHC complexes (3)(4)(5)(6), were fully characterized by electrospray ionization (ESI) mass spectrometry, IR, 1 H and 13 C NMR spectroscopies. In the ESI mass spectra of the bis(carbene) complexes 3 and 4, m/z values corresponding to both [MÀBr] 4 ] + for 4b) fragments were observed, with the latter as the base peak.…”
Section: Characterization Of Pd-nhc Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…4.6. 1,phenyl)imidazolium chloride (8) In a 100-mL round-bottomed flask, equipped with a magnetic stir bar and a rubber septum, N,N 0 -bis(2,6-diisopropyl-4-polyisobutylphenyl)ethylenediimine (6.3 g, 2.6 mmol) was dissolved in 25 mL of THF. Chloromethyl ethyl ether (0.25 g, 2.6 mmol) was added and the mixture was heated to 40 C for 20 h. The solvent was removed under reduced pressure and the residue was purified by column chromatography (eluted first with CH 2 Cl 2 and then with 9:1 solution of CH 2 Cl 2 and methanol).…”
Section: 6-diisopropyl-4-(polyisobutyl)aniline (6)mentioning
confidence: 99%
“…These properties led to many other studies that demonstrated that NHC-metal complexes have reactivities similar to those of phosphineemetal complexes, often with better air and moisture stability . NHC ligands can form stable bonds with metals and phosphineemetal complexes are sometimes used as precursors for NHC-metal complexes [7,8]. These properties of NHC ligands have led to many examples of metal complexes of these electron-rich ligands, NHC ligated complexes that are often used in homogeneous catalysis using transition metals like palladium, ruthenium, rhodium, gold, copper, and nickel [2].…”
Section: Introductionmentioning
confidence: 99%